Schizophycées littorales de la petite Syrte (Tunisie) récoltées par M. Seurat au cours de ses derniers voyages (1922-1923) - Gauthier-Lièvre, H. (Bulletin de la Société d'Histoire naturelle de l'Afrique du Nord, 1924)
Keywords: Entomologie – Djerba

Présence du caractère autogène chez Culex pipiens pipiens L. dans un biotope épigé de l’Ile de Djerba - Rioux, J. A.; Juminer, B.; Kchouk, M. (Archives de l'Institut Pasteur de Tunis, 1965)
Keywords: Entomologie – Djerba

Taxonomy of Saldula: revised genus and species group definitions, and a new species of the pallipes group from Tunisia (Heteroptera: Saldidae) - Polhemus, John T.; Lindskog, Per (Insect Systematics & Evolution, 1992)
A revised diagnosis of the genus Saldula Van Duzee based upon synapomorphic characters of male genitalia and hemelytral pigmentation patterns is given. According to this concept ca. 55% of the species World-wide currently assigned to Saldula will have to be transferred to other genera. Several new characters are employed in the definition of species and species groups. The species attributable to the pallipes species group are listed and supplemented by a brief overview of the taxonomic relationships of the Old World species. Saldula luteola sp. n. is described from coastal salt marshes on the Island of Djerba, Tunisia. It mainly appears in extremely depigmented morphs unparalleled elsewhere in the Saldidae and likely constitutes a sister-species of S. sardoa Filippi. The conspicuous intraspecific variation in body size and hemelytral pigmentation in S. palustris (Douglas), the closest relative of the former species, is depicted and briefly discussed. The descriptive accounts are accompanied by numerous photographic illustrations of somatic and genital characters.
Keywords: Entomologie – Djerba

Feeding ecology of some common intertidal neogastropods at Djerba (Tunisia) - Taylor, John D. (Vie et Milieu, 1987)
Keywords: Entomologie – Djerba

Uber den Wanderigel Erinaceus algirus Lereboullet 1842, von Djerba (Tunisien) (Mammalia: Insectivora: Erinaceidae) - Vesmanis, Indulis (1980)
Keywords: Entomologie – Djerba

Sur les ectoparasites du hérisson de Djerba - Weiss, Aloys (Archives de l’Institut Pasteur de Tunis, 1909)
Keywords: Entomologie – Djerba

Catalogue et distribution des arthropodes piqueurs de l’île de Djerba - Weiss, Aloys (Archives de l’Institut Pasteur de Tunis, 1909)
Keywords: Entomologie – Djerba

Sur l’existence, à Djerba, du phora chlorogastra Becker (Dipt. Phoridaé) et sur ses métamorphoses - Weiss, Aloys (Bulletin de la Société d’Histoire Naturelle de l'Afrique du Nord, 1911)
Keywords: Entomologie – Djerba

Seconde addition au catalogue des arthropodes piqueurs de l’ile de Djerba - Weiss, Aloys (Archives de l’Institut Pasteur de Tunis, 1913)
Keywords: Entomologie – Djerba

Troisième addition au catalogue des arthropodes piqueurs de l’ile de Djerba - Weiss, Aloys (Archives de l’Institut Pasteur de Tunis, 1913)
Keywords: Entomologie – Djerba

Diptères Asilides recueillis par M. A. Weiss dans l’île de Djerba (Tunisie). Description du Saropogon Weissii nov. sp. - Bezzi, M. (Bulletin du Muséum national d’histoire naturelle, 1911)
Keywords: Entomologie – Djerba